The Comparative Language Style at SOT and SOT’s Subtitle on Soft News DAAI Mandarin and Metro Xinwen - Dwi Adyla; Vivi Adryani Nasution, S.S., MTCSOL (Fakultas Sastra Universitas Darma Persada, 2021)
Nowadays, language style has entered a wider scope, included electronic journalism and also television news broadcast. This paper described and used language style according to Huang and friends (2012). This paper will discussed about the comparison of language style at soundbite on tape (SOT) and SOT’s subtitle on both soft news videos, is: DAAI Mandarin and Metro Xinwen. This paper’s goals is to find out the type of language style that contained in SOT and SOT’s subtitle on soft news DAAI Mandarin and Metro Xinwen. Data source using soft news video of television news broadcast. Research method used descriptive qualitative with observed data collection methods and note taking techniques for the data collection. The result of data analysis used three steps, is: data condensation, data presenting, and drawing conclusions. The results of data analysis are presented in the form of narrative explanation.